Cystinosis in Eastern Turkey - CESUR, YAŞAR; Dogan, Murat; Bulan, Keziban; Kaba, Sultan; Cesur, YAŞAR; CEYLANER, Serdar; Ustyol, Lokman (My University, 2016)
Background: This study was conducted to investigate CTNS (cystinosin, lysosomal cystine transporter) gene mutations and the clinical spectrum of nephropathic cystinosis among patients diagnosed with the disease in a single center in Turkey.